PENGARUHHPENGEMBANGAN SUMBERADAYA MANUSIAATERHADAP KINERJAAPETUGASSAVSEC DIIBANDAR UDARA SULTAN BABULLAH TERNATE - Usman, Muhammad Yusril S. (Relawan Jurnal Indonesia, 2022)
Regulation of the Director General of Civil Aviation Number: SKEP/2765/XXI/2010 Chapter 1 point 9 explains that Aviation Security is aviation security personnel who have (mandatory) have a license or certificate of officer proficiency (SKTP) who are given duties and responsibilities in the field of aviation security. . The main role of Avsec (Aviation Security) is the safety and security of passengers, flight crew, officers and the general public against unlawful acts by preventing the transportation of goods that can endanger the flight. This study is to answer whether there is an influence and how much influence the development of human resources has on the performance of avsec officers at Sultan Babullah Airport Ternate at Sultan Babullah Airport Ternate This study uses quantitative data. The data used in this study were taken from primary data based on questionnaires distributed to avsec officers with a total of 74 people, observation data and secondary data in the form of Standard Operational Procedure (SOP). The data analysis technique used is simple linear regression analysis, T test, correlation coefficient, and coefficient of determination. The results of hypothesis testing using the T-test show that there is a positive and significant effect with a tcount value of 8.490, a t-table value of 1.665 and the results of the Coefficient of Determination test show how much influence the X variable has on the Y variable, with a value of 0.500 or 50%, while the remaining 50% is caused by other factors. which were not investigated by the researcher.